The Impact of Systemic Bias in Media Literacy on Stunting Mitigation Efforts in Nias Barat - Azhar, Anang Anas; Sakdiah, Evi; Matondang, Abdul Rahman (The Islamic Education and Multiculturalism Foundation, 2024)
Stunting remains a critical public health issue in Indonesia, particularly in rural areas like Nias Barat, where limited access to resources and information exacerbates the problem. This study examines the systemic biases in media literacy and their impact on stunting prevention efforts in this underserved region. Using a Community-Based Participatory Research (CBPR) approach, the research integrates traditional communication channels such as local leaders and community meetings with media literacy initiatives to address cultural and infrastructural barriers. The mixed-methods methodology combines qualitative focus groups and interviews with quantitative surveys to assess changes in community awareness, health practices, and stunting prevalence. The findings highlight the need for culturally relevant and accessible health communication strategies, demonstrating that integrating media literacy with traditional channels enhances the reach and effectiveness of interventions. This study proposes an inclusive and sustainable framework for addressing stunting, offering valuable insights for policymakers and practitioners aiming to improve public health outcomes in marginalized regions